1985
DOI: 10.1111/j.1365-2230.1985.tb02547.x
|View full text |Cite
|
Sign up to set email alerts
|

Is Steroid tachyphylaxis preventable?

Abstract: Summary DNA synthesis in hairless mouse epidermis was studied during twice daily and 72‐hourly application regimes of Metosyn, Betnovate and Dermovate ointments, and of 0.05% fluocinonide solution, in order to determine a treatment schedule for continuous suppression of epidermal cell DNA synthesis. Tachyphylaxis occurred with all the twice daily regimes but not with the 72 hourly application regimes of Dermovate and Betnovate ointments during the time of study. The onset of tachyphylaxis was delayed when fiuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In clinical manifestations, tachyphylaxis is one of the greatest problems of steroid treatment. And as Clement et al demonstrated, tachyphylaxis was avoidable by employing a 72-hourly application regimen with some steroid ointments (6). In this experiment, we compared twice a week to daily applications with regard to long-term systemic effects.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In clinical manifestations, tachyphylaxis is one of the greatest problems of steroid treatment. And as Clement et al demonstrated, tachyphylaxis was avoidable by employing a 72-hourly application regimen with some steroid ointments (6). In this experiment, we compared twice a week to daily applications with regard to long-term systemic effects.…”
Section: Discussionmentioning
confidence: 91%
“…Differences in application schedules may cause significant differences in the systemic and topical effects of these steroids. Clement (6), for example, reported that tachyphylaxis did not occur with 72-hour schedules, although it did with some twice daily routines. Woodford et al (7) contended that once daily application was clinically the most advantageous.…”
Section: Introductionmentioning
confidence: 99%